Using screening data: Educators’ perceptions of a structured data review - Grubb, Justina; Young, Ellie L. (Frontiers in Education, 2024)
Schoolwide social-emotional screening identifies students who may be at-risk for school problems and benefit from prevention efforts, additional supports, or individualized interventions. Data from screening can also pinpoint topics that bolster teachers' knowledge and skills when they provide supports and instruction focused on social, emotional, and behavioral needs. While research has explored many aspects of schoolwide screening, studies that focus on how the process of summarizing and using screening data are limited. This study investigated school teams' perspectives on the use of a structured guide for reviewing their screening data.After collecting schoolwide screening data, 47 participants from seven school leadership teams used a Discussion Guide (DG) to answer a series of questions about their Student Risk Screening Scale -Internalizing and Externalizing (SRSS-IE) data. Using content analysis, this qualitative study identified what teams found helpful, less helpful, and what they might add to the DG. Participants valued the DG's usefulness in developing data-based responses to the SRSS-IE results and identifying patterns and trends in their data. Including a menu of specific intervention strategies and supports was a frequent suggestion for improving the DG. Reviewing their screening data took longer than expected; participants recommended that teams needed multiple meetings for organizing, analyzing, and developing action plans.